2015
DOI: 10.1007/s00216-015-9093-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and characterization of alkaloids from roots of Rauwolfia serpentina using ultra-high performance liquid chromatography-photo diode array-mass spectrometry

Abstract: A new UHPLC-UV method has been developed for the simultaneous analysis of seven alkaloids [ajmaline (1), yohimbine (2), corynanthine (3), ajmalicine (4), serpentine (5), serpentinine (6), and reserpine (7)] from the root samples of Rauwolfia serpentina (L.) Benth. ex Kurz. The chromatographic separation was achieved using a reversed phase C18 column with a mobile phase of water and acetonitrile, both containing 0.05% formic acid. The seven compounds were completely separated within 8 min at a flow rate of 0.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…The product had an m / z of 371.1967, and also appeared to undergo dehydration ( m / z 353) during mass spectrometry (Figure S3). The fragmentation pattern indicated that the compound contains an indole moiety, with the typical 144 fragment observed for other indole alkaloids . In addition, a fragment of 342, which could potentially arise from the loss of a CH 2 O functional group, was observed.…”
Section: Resultsmentioning
confidence: 98%
“…The product had an m / z of 371.1967, and also appeared to undergo dehydration ( m / z 353) during mass spectrometry (Figure S3). The fragmentation pattern indicated that the compound contains an indole moiety, with the typical 144 fragment observed for other indole alkaloids . In addition, a fragment of 342, which could potentially arise from the loss of a CH 2 O functional group, was observed.…”
Section: Resultsmentioning
confidence: 98%
“…Separation of MIAs was reported within 23–50 min. in different Rauwolfia species using high performance liquid chromatography‐quadrupole time of flight‐mass spectrometry . The present method has good separation in 10 min time, high mass resolution, and mass accuracy with MS n facility .…”
Section: Resultsmentioning
confidence: 92%
“…Compounds 3 and 6 showed common fragment ions at m/z 160 and 174. Similarly, compounds 1 , 7 , 9 , 10 and 12 showed common fragment ions at m/z 170, 158 and 144 due to loss of terpene moiety via C ‐ring cleavage .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Among all indole alkaloids, reserpine (antihypertensive agent) from Rauvolfia serpentine (Sagi et al, 2016), vinblastine and vincristine (antitumor lead) from Catharanthus roseus (El-Sayed and Verpoorte, 2007) are the most significant. Other indole alkaloids also possess essential and potent pharmacological activities such as antimicrobial, antifungal, CNS stimulant, antiviral.…”
Section: The Biological Activity Of Indole Alkaloidsmentioning
confidence: 99%